Nýrnafrumukrabbamein á Íslandi : yfirlitsgrein - Ásgeir Thoroddsen; Guðmundur Vikar Einarsson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Renal Cell Carcinoma (RCC) is by far the most common malignant tumor of the kidney. It is a disease with many faces, known for its clinical diversity and often unpredictable behavior. Less is known about its etiology and risk factors than for most other human cancers. Mortality-to-incidence ratio is higher compared to other urologic malignancies, and the malignancy confers adverse prognosis for the majority of patients. At the same time as incidence of RCC has been rising globally, progress has been made in the understanding of the disease, especially within the field of genetics and biological research. Immunotherapies together with tyrosine kinase inhibitors and growth factor/angiogenesis modulators are being developed for patients with advanced disease and improvements have been made in the surgical approach. This, together with increased incidental detection secondary to the widespread use of modern imaging procedures, suggests improved prognosis of these patients in the future. For unknown reasons the incidence of RCC is higher in Iceland than in most other countries, about 30 new cases being diagnosed every year, with 14 deaths due to RCC occurring. This evidence-based article reviews major studies on different aspects of RCC with special emphasis on the epidemiology and clinicopathological presentation of the disease in Iceland. Nýrnafrumukrabbamein er langalgengasta illkynja æxlið í nýrum og nýgengi þess er vaxandi víðast hvar í heiminum. Á síðustu tveimur áratugum hefur þekking á nýrnafrumukrabbameini aukist verulega, ekki síst skilningur á erfða- og ónæmisfræði sjúkdómsins. Engu að síður er lítið vitað um orsakir og áhættuþætti samanborið við mörg önnur krabbamein. Þetta á ekki síst við um tengsl erfða við nýrnafrumukrabbamein. Sjúkdómurinn getur verið nánast einkennalaus og margir greinast með langt genginn sjúkdóm, þar sem langtímahorfur eru mun lakari en þegar um staðbundið krabbamein er að ræða. Á ...